2012
DOI: 10.1080/15381501.2012.735164
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Adherence Among Rural Indian Women Living With HIV/AIDS

Abstract: In this prospective, randomized clinical trial, correlates of adherence to antiretroviral therapy (ART) were assessed using a baseline questionnaire among 68 rural women living with AIDS (WLA) in India. Unadjusted analyses revealed positive relationships of ART adherence with Hindu religion, and support from spouses and parents, whereas negative associations were found with depression, poor quality of life, and having ten or more HIV symptoms. Multiple linear regression analysis also revealed that WLA who were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 43 publications
2
14
0
2
Order By: Relevance
“…The impact of the program on the physical health of WLA was also reported by the women in terms of CD4 counts and body weight and concur with other research studies (Nyamathi, Hanson, et al, 2012; Nyamathi, Salem, Ernst, Keenan, Suresh, Sinha, Ganguly, Ramakrishnan, & Liu, 2012). …”
Section: Discussionsupporting
confidence: 89%
“…The impact of the program on the physical health of WLA was also reported by the women in terms of CD4 counts and body weight and concur with other research studies (Nyamathi, Hanson, et al, 2012; Nyamathi, Salem, Ernst, Keenan, Suresh, Sinha, Ganguly, Ramakrishnan, & Liu, 2012). …”
Section: Discussionsupporting
confidence: 89%
“…An investigation by Nyamathi et al [79] used measures of internalized stigma, enacted stigma, vicarious stigma (i.e., hearing stories of enacted stigma targeting others), and felt stigma (i.e., perception of stigma in the community). In this investigation, the authors found that although internalized and vicarious stigma had univariate associations with adherence, as assessed by observed pill counts, neither was significantly associated with adherence in multivariate analyses, after including depression and adherence support from parents.…”
Section: Studies Using Multiple Measures Of Stigmamentioning
confidence: 99%
“…Social support has been associated with higher adherence (Nyamathi et al, 2012; Shah et al, 2007), and depression is linked with poorer adherence (Anuradha et al, 2013; Nyamathi et al, 2012; Sarna et al, 2008). Although stigma has been associated with poor adherence in many settings (Kingori et al, 2012; Rao, Kekwaletswe, Hosek, Martinez, & Rodriguez, 2007; Rintamaki, Davis, Skripkauskas, Bennett, & Wolf, 2006; Vyankandondera et al, 2013) and noted as a barrier in qualitative studies (Joglekar et al, 2011; Kumarasamy et al, 2005), it has not been quantitatively assessed in India.…”
Section: Introductionmentioning
confidence: 99%